Internal Corporate Social Responsibility: between the social imaginary and the real. - Gutiérrez Calderón, María Alexandra (2022)
In an ever-changing world, with new challenges to be assumed, with more complex and innovative organizational dynamics that demand higher levels of productivity, long working hours, over increasingly attenuating workloads, require a rethinking of thoughts and beliefs that allow the establishment of environmental and instrumental conditions for the achievement of business objectives. This article seeks to make a reflection and contribute to the constructive dialogue on internal social responsibility, bearing in mind the function that social imaginaries fulfill in its construction, moving away a little from the look of the social and economic as it has been traditionally analyzed, but rather being productive in the construction of policies at the level of human talent management and the practices of internal CSR.